2023
DOI: 10.3389/fendo.2023.1144331
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers and prediction of upstream miRNAs in diabetic nephropathy

Abstract: ObjectiveTo explore biomarkers of diabetic nephropathy (DN) and predict upstream miRNAs.MethodsThe data sets GSE142025 and GSE96804 were obtained from Gene Expression Omnibus database. Subsequently, common differentially expressed genes (DEGs) of renal tissue in DN and control group were identified and protein-protein interaction network (PPI) was constructed. Hub genes were screened from in DEGs and made an investigation on functional enrichment and pathway research. Finally, the target gene was selected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…MMP2 is recognized as a biomarker of DKD fibrosis. Yin et al [28] found that miR-106b-5p and miR-93-5p can act as upstream signal regulators to regulate the expression of MMP2 and participate in the process of DKD fibrosis. Circ_0114428 and Circ_0123996 promote the progression of DN by regulating the miR-203a-3p/ SOX6 and miR-185-5p/SMAD3 axes to promote high glucose-induced glomerular mesangial cell proliferation, fibrosis, and EMT processes [29,30] .…”
Section: Research Progress Of Mirnas In Renal Fibrosis In Dnmentioning
confidence: 99%
“…MMP2 is recognized as a biomarker of DKD fibrosis. Yin et al [28] found that miR-106b-5p and miR-93-5p can act as upstream signal regulators to regulate the expression of MMP2 and participate in the process of DKD fibrosis. Circ_0114428 and Circ_0123996 promote the progression of DN by regulating the miR-203a-3p/ SOX6 and miR-185-5p/SMAD3 axes to promote high glucose-induced glomerular mesangial cell proliferation, fibrosis, and EMT processes [29,30] .…”
Section: Research Progress Of Mirnas In Renal Fibrosis In Dnmentioning
confidence: 99%